Development of Water Shortage Risk Maps for Agricultural Production and Maps of Winter-Spring Cultivation Schedule in the Midland and Northern Delta Region - Institute of Water Resources Planning, Vietnam (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
The reports cover the development of Climate-Smart Maps and Adaptation Plans (CS-MAP) for the 12 provinces in the Midland and Northern Delta Region of Vietnam. Using CS-MAP, the reports tackle the development of: water shortage risk maps for agricultural production; maps of the winter - spring rice cultivation schedule for the 12 provinces in the study area, ensuring consistency among provinces, creating favorable conditions for the increased discharge of water from hydroelectric reservoirs, and saving of water; and maps of areas that need to change crop structure in winter-spring crop in the 12 provinces to adapt to the water situation.